Challenges Posed by Immune Responses to AAV Vectors: Addressing Root Causes - Hamilton, Bradley A.; Wright, J. Fraser (Frontiers in Immunology, 2021)
Host immune responses that limit durable therapeutic gene expression and cause clinically significant inflammation remain a major barrier to broadly successful development of adeno-associated virus (AAV)-based human gene therapies. In this article, mechanisms of humoral and cellular immune responses to the viral vector are discussed. A perspective is provided that removal of pathogen-associated molecular patterns in AAV vector genomes to prevent the generation of innate immune danger signals following administration is a key strategy to overcome immunological barriers.